Using GPUs for beamforming acceleration on SAFT imaging - Romero, D.; Martínez-Graullera, O.; Martín, C. J.; Higuti, R. T. [UNESP]; Octavio, A. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
SAFT techniques are based on the sequential activation, in emission and reception, of the array elements and the post-processing of all the received signals to compose the image. Thus, the image generation can be divided into two stages: (1) the excitation and acquisition stage, where the signals received by each element or group of elements are stored; and (2) the beamforming stage, where the signals are combined together to obtain the image pixels. The use of Graphics Processing Units (GPUs), which are programmable devices with a high level of parallelism, can accelerate the computations of the beamforming process, that usually includes different functions such as dynamic focusing, band-pass filtering, spatial filtering or envelope detection. This work shows that using GPU technology can accelerate, in more than one order of magnitude with respect to CPU implementations, the beamforming and post-processing algorithms in SAFT imaging. ©2009 IEEE.
Keywords: Array elements; Band pass filtering; Dynamic focusing; Envelope Detection; Graphics processing units; Image generations; Image pixels; Order of magnitude; Post processing; Postprocessing algorithms; Programmable devices; Received signals; Sequential Activation; Spatial filterings; Two stage; Program processors; Synthetic apertures; Ultrasonics; Beamforming